ANALISIS STABILITAS LERENG PADA RUAS JALAN BLANGKEJEREN - AWEAUNAN KABUPATEN GAYO LUES PROVINSI NANGGROE ACEH DARUSSALAM - Hendra Gunawan; Banta Chairullah; Devi Sundary (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
Roads Blangkejeren - Laweaunan is a one-lane road transport in the Province ofNanggroe Aceh Darussalam, which has an altitude slopes varying between 3.5 to 4.3 m. Earthquakes, rainfall and altitude slopes greatly affect the stability of the slopes on theseroads. The stability analysis aims to obtain a slope stability conditions that meet safety requirements at Jalan Blangkejeren - Laweaunan Gayo Lues District of Nanggroe Aceh Darussalam. Slope stability design using the simplified Bishop method and Plaxissoftware. The use of these methods has given the ease and accuracy in solving the problem of stability of the slope to meet the security requirements of slope stability. Based on the analysis of the simplified Bishop method and Plaxis at Jalan Blangkejeren - Laweaunan STA. 03 + 650, STA. 03 + 700, and STA. 03 + 750 which has a slope of each 63,4°(1H: 2V) concluded that the slope is not safe, so it needs a change of slope. After the change of slope on the slopes of the results showed that the slope of 30°-24°, the slope of qualified safety with a safety factor (STA. 03 + 650), from 1.299 to 1.468 (STA. 03 + 700) from 1.346 to 1.515 (STA. 03 + 750). Based on the results of the slope stability analysis obtained slope collapse semicircular arc (rotational sliding). The slope stability are qualified security that permitted 1 as recommended by Abramson (1996)